تطبيق القاموس المساعد " أحب اللغة العربية " لاستيعاب المفردات العربية لدى التلاميذ المدرسة الإبتدائية مفتاح العلوم جورنوان كتفانج سمفاج مدورا - Marwaki (Muhadasah: Jurnal Pendidikan Bahasa Arab, 2019)
This study is about the implementation of an assisted dictionary“ I love Arabic for elementary school level at Islamic Elementery school of Miftahul Ulum Jurnuan Bunten Timur Ketapang Sampang. The porpuse of this study is to make students easy studying Arabic. The method used is a type of descriptive approach. The technique used to collect data is observation, interviews, and documentation. The scope of the study are students who study Arabic at Islamic Elementery school of Miftahul Ulum Jurnuan Bunten Timur Ketapang Sampang. The data source is the student of elementery school, Arabic teacher. The results of this study make students easiyer in understanding text Arabic, speaking Arabic, and memorizing Arabic.